FROM SOCIAL JUSTICE TO POLITICAL EQUALITY: AMBEDKAR’S DEMOCRATIC DREAM - Kumar, Manoj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Dr. Bhimrao Ramji Ambedkar’s democratic vision does not limit Indian democracy to mere electoral processes and institutional structures, but defines it as a way of life based on social justice, equality, and fraternity. According to him, political equality cannot be meaningful unless the deeply ingrained caste discrimination, economic inequality, and social exclusion in society are eradicated. In the Constituent Assembly, he warned that India was entering a "life of contradictions"—where there would be equality in politics, but inequality in socio-economic life would persist. Ambedkar considered democracy "a way of life" that embodies the values ​​of liberty, equality, and fraternity. He considered measures such as constitutional morality, social justice, affirmative action, land reforms, labor rights, and universal education essential for making political democracy lasting and meaningful. His approach, departing from both liberal and Marxist traditions, placed caste oppression at the center and emphasized social democracy as the foundation of political democracy. This paper analyzes Ambedkar’s democratic philosophy and argues that the depth and sustainability of democracy in India is possible only on the foundation of social justice. Even today, when caste discrimination, economic inequality, and challenges to political representation persist, Ambedkar’s democratic vision provides guiding principles for strengthening and revitalizing democracy in the 21st century